Crisis-Driven Rebranding and Narrative Strategy: The Transformation of Kutus Kutus into Sanga Sanga - Latifa Ramonita; Deddy Muharman; Chelma Destria; Eka Bella Ferlinda Furkan (Yayasan Ilomata, 2026)
Rebranding often becomes a strategic imperative, not merely an option, especially when a brand faces massive internal crises and market challenges. This qualitative study examines the rebranding strategy employed by Babe Bambang Pranoto, founder of PT Kutus-Kutus Herbal, in transforming the brand from